Sub-100-nm Nearly Monodisperse n-Paraffin/PMMA Phase Change Nanobeads - Ho Young Woo; Da Won Lee; Tae Yeol Yoon; Jong Bae Kim; Ji-Yeon Chae; Taejong Paik (Nanomaterials, 2021)
In this study, we demonstrate the colloidal synthesis of nearly monodisperse, sub-100-nm phase change material (PCM) nanobeads with an organic n-paraffin core and poly(methylmethacrylate) (PMMA) shell. PCM nanobeads are synthesized via emulsion polymerization using ammonium persulfate as an initiator and sodium dodecylbenzenesulfonate as a surfactant. The highly uniform n-paraffin/PMMA PCM nanobeads are sub-100 nm in size and exhibit superior colloidal stability. Furthermore, the n-paraffin/PMMA PCM nanobeads exhibit reversible phase transition behaviors during the n-paraffin melting and solidification processes. During the solidification process, multiple peaks with relatively reduced phase change temperatures are observed, which are related to the phase transition of n-paraffin in the confined structure of the PMMA nanobeads. The phase change temperatures are further tailored by changing the carbon length of n-paraffin while maintaining the size uniformity of the PCM nanobeads. Sub-100-nm-sized and nearly monodisperse PCM nanobeads can be potentially utilized in thermal energy storage and drug delivery because of their high colloidal stability and solution processability.